2017
DOI: 10.1111/btp.12429
|View full text |Cite
|
Sign up to set email alerts
|

Active background choice facilitates crypsis in a tropical crab

Abstract: Animals can evade predators in multiple ways, one of the most effective of which is to avoid detection in the first place. We know much about the evolution of color patterns that match the visual background to avoid detection (i.e., crypsis), yet we know surprisingly less about the specific behaviors that have co‐evolved with these morphological traits to enhance or maintain crypsis. We here explore whether the match between body color and background in a seemingly well‐camouflaged tropical shore crab is a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This is seemingly in contrast with the results here. However, there is growing evidence in many animal taxa including crabs that individuals of different appearance from within a species choose where to rest in order to improve camouflage in their respective habitats (Kang, Moon, Lee, & Jablonski, 2012;Kettlewell & Conn, 1977;Kjernsmo & Merilaita, 2012;Lovell, Ruxton, Langridge, & Spencer, 2013;Marshall, Philpot, & Stevens, 2016;Sargent, 1966;Uy et al, 2017; reviewed by Stevens & Ruxton, 2018). Otherwise, it is hard to explain very local level phenotype-substrate associations of crabs without the role of behavioural background selection (Nokelainen, Hubbard et al, 2017;Nokelainen, Stevens, & Caro, 2017;Todd et al, 2012 Note.…”
Section: Discussionmentioning
confidence: 99%
“…This is seemingly in contrast with the results here. However, there is growing evidence in many animal taxa including crabs that individuals of different appearance from within a species choose where to rest in order to improve camouflage in their respective habitats (Kang, Moon, Lee, & Jablonski, 2012;Kettlewell & Conn, 1977;Kjernsmo & Merilaita, 2012;Lovell, Ruxton, Langridge, & Spencer, 2013;Marshall, Philpot, & Stevens, 2016;Sargent, 1966;Uy et al, 2017; reviewed by Stevens & Ruxton, 2018). Otherwise, it is hard to explain very local level phenotype-substrate associations of crabs without the role of behavioural background selection (Nokelainen, Hubbard et al, 2017;Nokelainen, Stevens, & Caro, 2017;Todd et al, 2012 Note.…”
Section: Discussionmentioning
confidence: 99%
“…Together with our findings that red pattern does not differ with beetle length, this suggests that the less common adoption of a typical conspicuous color, red, by polyphagous species, could be to limit conspicuousness when they feed on diverse backgrounds. Recent studies of lizards (Marshall et al, 2016) and crabs (Uy et al, 2017) indicate that animals actively choose to match their background. As the spectral sensitivities of chrysomelids appear to be limited to UV, blue and green but not red (Sharkey et al, 2017), active background matching may not fully explain color pattern differences of beetles with their host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, work on ghost crabs by Uy et al . () showed that darker and lighter crabs preferred darker and lighter backgrounds, respectively. However, these crabs were also much more likely to originate from darker and lighter sandy parts of the beach, respectively, meaning that they could have imprinted on their original background.…”
Section: Mechanisms Of Choice and Orientationmentioning
confidence: 99%
“…Recent work by Uy et al . () showed that lighter and darker individual pallid ghost crabs ( O. pallidula ) choose light and dark sand, respectively, in behavioural trials, whereas intermediate crabs show no preference.…”
Section: Background Choicementioning
confidence: 99%
See 1 more Smart Citation